“En la Argentina no hay lingüistas”. Profesionalización e institucionalización en el epistolario entre María Beatriz Fontanella de Weinberg y Guillermo Guitarte (1962-1991) - Ennis, Juan Antonio; Santomero, Lucila (Pontificia Universidad Católica del Perú, 2025)
This paper aims to provide a concise account of the progress made in the study of the correspondence sustained over nearly three decades (1962- 1991) between the Argentine linguist María Beatriz Fontanella de Weinberg, professor and researcher at the Universidad Nacional del Sur (Bahía Blanca), and her colleague —and in many regards mentor— Guillermo Guitarte, who at the start of their epistolary exchange was already based abroad, first briefly in Colombia and then in the United States. These letters not only document the exchange concerning the specific research issues of both correspondents, but also their perception of the conditions that would allow for the institutionalization of scientific practice in the area of linguistics in the country during the period in question.

Este trabajo se propone dar cuenta sintética de los avances en el estudio de la correspondencia sostenida por casi tres décadas (1962-1991) entre la lingüista argentina María Beatriz Fontanella de Weinberg, docente e investigadora en la Universidad Nacional del Sur, Bahía Blanca; y su colega, y en muchos aspectos maestro, Guillermo Guitarte, radicado a partir del comienzo de este epistolario en el extranjero, primero brevemente en Colombia y luego en Estados Unidos. En estas cartas, no solo se documenta el intercambio relativo a los problemas específicos de investigación de ambos corresponsales, sino también la percepción de las condiciones de posibilidad para la institucionalización de la práctica científica en el área de la lingüística en el país en el período señalado.
“There Are No Linguists in Argentina.” Professionalization and Institutionalization in the Correspondence between María Beatriz Fontanella de Weinberg and Guillermo Guitarte (1962–1991)
Keywords: Correspondence; Fontanella de Weinberg; Guitarte; Linguistics; Correspondencia; Fontanella de Weinberg; Guitarte; Lingüística; https://purl.org/pe-repo/ocde/ford#6.02.06